2008
DOI: 10.1038/ja.2008.94
|View full text |Cite
|
Sign up to set email alerts
|

A New 24-membered Lactone and a New Polyene δ-Lactone from the Marine Bacterium Bacillus marinus

Abstract: A new 24-membered macrolide macrolactin T (1), and a new polyene d-lactone macrolactin U (2), along with macrolactins A, B, D, O, and S, were isolated from the cultured broth of the bacterium Bacillus marinus, which was isolated from Suaeda salsa collected in the coastline of Bohai Sea of China. The structures of 1 and 2 were elucidated on the basis of extensive spectroscopic data analyses. The inhibitory activity of macrolactins T, B and D against fungi Pyricularia oryzae and Alternaria solani, and bacteria S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 9 publications
4
32
0
Order By: Relevance
“…Fermentation broths of B-9987/sfp followed by extraction and HPLC analysis showed that overexpression of sfp led to increment of the macrolactin A production to 29 mg L 1 ( Figure 4A, panel iii), which is about 1.6-fold as compared to that of the wild type strain (18 mg L 1 ) ( Figure 4A, panel ii). The identity of macrolactin A was determined by comparison with the standard [5] (Figure 4A, panel i), exhibiting the same retention time and UV spectrum ( Figure 4B) Figure 4C). As a result, the biocontrol efficacy of B-9987/sfp could probably be enhanced, indicating this strategy would potentially be applicable to improvement of other biocontrol strains.…”
Section: Overexpression Of the Phosphopantetheinyl Transferase Gene Smentioning
confidence: 99%
See 1 more Smart Citation
“…Fermentation broths of B-9987/sfp followed by extraction and HPLC analysis showed that overexpression of sfp led to increment of the macrolactin A production to 29 mg L 1 ( Figure 4A, panel iii), which is about 1.6-fold as compared to that of the wild type strain (18 mg L 1 ) ( Figure 4A, panel ii). The identity of macrolactin A was determined by comparison with the standard [5] (Figure 4A, panel i), exhibiting the same retention time and UV spectrum ( Figure 4B) Figure 4C). As a result, the biocontrol efficacy of B-9987/sfp could probably be enhanced, indicating this strategy would potentially be applicable to improvement of other biocontrol strains.…”
Section: Overexpression Of the Phosphopantetheinyl Transferase Gene Smentioning
confidence: 99%
“…Bacillus marinus B-9987 was isolated from the rhizosphere of Suaeda salsa collected in the intertidal zone of Bohai Bay of Eastern China [2]. Chemical investigations revealed that B. marinus B-9987 is capable to produce a variety of antimicrobial secondary metabolites [35], such as macrolactins (Figure 1), which are able to inhibit the growth of plant fungal pathogens Pyricularia oryzae and Alternaria solani by destroying their cell walls [5]. Besides antifungal activity, macrolactins also exhibit antibacterial, antiviral, anticancer, anti-inflammatory, and as well as antiangiogenic activities [69].…”
mentioning
confidence: 99%
“…The structures of 3-5 were established by analyzing their 1D NMR spectral data and by comparison with the literature. 5,6 Compound 1 had the molecular formula of C 24 H 34 O 6 as deduced from NMR spectra and HR-ESI-MS. 13 ) were obviously observed in the NMR spectra of 1, which should be caused by the change of the three-dimensional effect at C-7 position, and suggested that the configuration of ÀOH at C-7 in 1 should be a-configuration instead of b-configuration as it existed in 2 and other previously isolated macrolactins. 4,[7][8][9][10][11][12][13] The suggestion was supported by the NOESY (Figure 3), in which NOE correlations of H-6b with H-8/H-4 and H-7 with H-8 were observed, whereas no NOE correlations between H-7 and H-9/H-5 were observed, which were in agreement with the MM2 optimized conformation of 1.…”
mentioning
confidence: 85%
“…4,[7][8][9][10][11][12][13] Some of these compounds showed strong antibacterial, anti-tumor, and antivirus activities. 4,7,[9][10][11][12][13] The antibacterial activity of 1-5 against four bacterial strains and the antilarval activity of 3-5 against larval settlement of Bugula neritina and Balanus amphitrite larvae were evaluated. This paper deals with the isolation, structural elucidation of 1 and biological activity of 1-5.…”
mentioning
confidence: 99%
“…1,2) The strain Bacillus marinus B-9987, isolated from Suaeda salsa in Bohai coastline of P. R. China, has shown excellent activity against phytopathogens both in vitro and in vivo, 3,4) and some antimicrobial macrolactin constituents 5) have been isolated from this strain. In order to screen more constituents by bio-guided isolation, we have obtained two new cyclic lipopeptides maribasins A (1) and B (2) (Fig.…”
mentioning
confidence: 99%